The prospect of using palm wine as a fluid loss control agent in water based drilling mud (2016)
The need to advance and project the use of local materials as suitable drilling fluid additive in the oil and gas industry in Nigeria led to the research on the possible use of palm wine and potash as additives in a water base drilling mud. A comparative study of these local materials (palm wine and potash) with imported foreign materials (lignite and caustic soda) as control were used in investigating the properties of a water base drilling fluid. A laboratory investigation of the effects of temperature and aging time on the properties of water-base drilling fluid is made with Fann Model 800 High Temperature and a High Pressure (HTHP) Viscometer, according to the API recommended standard practice. The results obtained showed similarity in the drilling fluid’s rheological and filtration properties; mud weight and pH values for both local and foreign additives. The result from the mud sample prepared from the palm wine and potash had apparent viscosity, plastic viscosity and yield point decreasing steadily with increase in temperature for all aging time just as shown with the control sample, while the aging effect diminishing as the aging time increases. The potash was seen to have increased the mud pH from 7.0 to 12.9 pH units. The results, shows that both palm wine and potash can be used as suitable in water base drilling mud additive.